Sexual sensation seeking, coping styles, social stress and their association with adolescent sexual behaviour - Teva, Inmaculada; Bermúdez, María Paz; Buela Casal, Gualberto (Anales de Psicología / Annals of Psychology, 2010)
The aim of this study is to make a theoretical review of the period of years from 1998 to 2007 about the influence of coping styles, social stress and sexual sensation seeking on sexual risk behaviours in adolescents and to report about prevalence of sexual behaviours in adolescents. It is a theoretical study. Literature search was made using electronic data bases and a manual search in specialized journals. In seven articles, associations among sexual behaviour, sexual sensation seeking and coping were found. Studies published about associations among adolescent sexual behaviour and coping, social stress and sexual sensation seeking are scarce. It is emphasized future research about these associations and to carry out longitudinal studies. In 44 articles about prevalence of sexual behaviour information about onset of sexual intercourse, adolescents with sexual intercourse experience, sexual practices, number of sexual partners and condom use and use of other contraceptives were described. The highest number of articles has been published in the United States and cross-sectional studies were predominant.